Diacylglycerol Kinases (DGKs): Novel Targets for Improving T Cell Activity in Cancer - Riese, Matthew J.; Moon, Edmund K.; Johnson, Bryon D.; Albelda, Steven M. (Frontiers in Cell and Developmental Biology, 2016)
Diacylglycerol kinases (DGKs) are a family of enzymes that catalyze the metabolism of diacylglycerol (DAG). Two isoforms of DGK, DGKα and DGKζ, specifically regulate the pool of DAG that is generated as a second messenger after stimulation of the T cell receptor (TCR). Deletion of either isoform in mouse models results in T cells bearing a hyperresponsive phenotype and enhanced T cell activity against malignancy. Whereas DGKζ appears to be the dominant isoform in T cells, rationale exists for targeting both isoforms individually or coordinately. Additional work is needed to rigorously identify the molecular changes that result from deletion of DGKs in order to understand how DAG contributes to T cell activation, the effect of DGK inhibition in human T cells, and to rationally develop combined immunotherapeutic strategies that target DGKs.